HIERARCHICAL CAPACITY-BUILDING STRATEGY THROUGH RECURRENT TRAINING FOR ROTARY WING (HELICOPTER) PILOTS IN INDONESIAN NATIONAL POLICE AIR POLICE DIRECTORATE - Dira Fitria Setyoningrum; Mala Sondang Silitonga (DIA: Jurnal Administrasi Publik, 2025)
This study aims to describe the hierarchical capacity-building strategy for helicopter (rotary wing) pilots in the Air Police Directorate through recurrent training. Human capital theory and capacity development theory used as analytical tools to examine the data collected. This research employs a descriptive qualitative approach. Informants include individuals involved in policy formulation, implementation, and evaluation of recurrent training for INP Air Police Directorate’s first-line officers. The study finds that recurrent training for Air Police Directorate’s rotary wing pilots faces several significant challenges, including infrastructure limitations, training cooperation issues, and high pilot mobility. The strategy employed to optimize this training involves using helicopter simulators, which are currently under development. With the availability of such facilities, the management of pilot resources can be tailored to specific training needs according to the applicable functional positions.